(3efJgi GdeOGQc hefJgi dH cd cGed hYGQa hSGdcs - (3SYO GdOjf SYO GdaQZGfis; (3YeQ Hf Ydj Hf GdaGQV GdMehj, CHh MaU,J (B576 (3g` s ((3YJjb Hf YHO Gddg Hf YJjb GdJejei GdegOhi s)
(3ChdgG (B:s
(3CeG HYO aEfg deG cGfJ GdCMcGe GdSGHZI JfHfi YdjgG GdCbSGe GddGMbI s
(3BNQgG (B:s
(3jfJgi HTQM GdHjJ (B: (3hbO UQJ CQLhG eG jNGa aCSYOi Hg QhM ejJ ddMjGI ESJYOJ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeY GdCMeOi HWfWG (B((3JUha (B125) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs